Wigner-like crystallization of Anderson-localized electron systems with low electron densities - Slutskin, A. A.; Pepper, M.; Kovtun, H. A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2002)
We consider an electron system under conditions of strong Anderson localization, taking into account interelectron long-range Coulomb repulsion. We establish that at sufficiently low electron densities and sufficiently low temperatures the Coulomb electron interaction brings about ordering of the Anderson-localized electrons into a structure that is close to an ideal (Wigner) crystal lattice, provided the dimension of the system is > 1. This Anderson-Wigner glass (AWG) is a new macroscopic electron state that, on the one hand, is beyond the conventional Fermi glass concept, and on the other hand, qualitatively differs from the known "plain" Wigner glass (inherent in self-localized electron systems) in that the random slight electron displacements from the ideal crystal sites essentially depend on the electron density. With increasing electron density the AWG is found to turn into the plain Wigner glass or Fermi glass, depending on the width of the random spread of the electron levels. It is shown that the residual disorder of the AWG is characterized by a multi-valley ground-state degeneracy akin to that in a spin glass. Some general features of the AWG are discussed, and a new conduction mechanism of a creep type is predicted.